1997
DOI: 10.1097/00006123-199712000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Use of Cerebrospinal Fluid Shunts in Patients Having Acquired Immunodeficiency Syndrome with Cryptococcal Meningitis and Uncontrollable Intracranial Hypertension

Abstract: Patients with acquired immunodeficiency syndrome who develop cryptococcal meningitis and who suffer serious visual loss or ocular palsies with elevated pressures should be considered for cerebrospinal fluid shunting at an early stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
77
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 7 publications
0
77
0
Order By: Relevance
“…Uncontrollable ICH due to cryptococcal meningitis in patients with AIDS plays an important role in morbidity and mortality 14 . In a recent study, Souza et al…”
mentioning
confidence: 99%
“…Uncontrollable ICH due to cryptococcal meningitis in patients with AIDS plays an important role in morbidity and mortality 14 . In a recent study, Souza et al…”
mentioning
confidence: 99%
“…In addition, several reports of C. neoformans infection of polytetrafluoroethylene peritoneal dialysis fistula and prosthetic cardiac valves highlight the ability of this organism to adhere to medical devices (6,7,26). In fact, the increasing use of ventriculoperitoneal shunts to manage intracranial hypertension associated with cryptococcal meningoencephalitis highlights the importance of investigating the biofilm-forming properties of this organism (2,13).…”
mentioning
confidence: 99%
“…For instance, Walsh et al reported that C. neoformans could form biofilms in ventriculoatrial shunt catheters (27). The increasing use of ventriculoperitoneal shunts to manage intracranial hypertension associated with cryptococcal meningoencephalitis highlights the importance of investigating the biofilm-forming properties of this organism (2). Moreover, biofilm formation has profound consequences in the establishment of fungal infection and is associated with persistent infection since biofilms increase resistance to host immune mechanisms and antimicrobial therapy (7).…”
mentioning
confidence: 99%